VD_FINDINFO HC / 2014 / 154 vom 14. Februar 2014 - VD Tribunal cantonal (2014)
OBLIGATION D'ENTRETIEN, ENFANT, REVENU D'UNE ACTIVITÉ LUCRATIVE INDÉPENDANTE, VALEUR LOCATIVE | 173 al. 3 CC, 176 al. 1 ch. 1 CC, 308 al. 1 let. b CPC (CH), 308 al. 2 CPC (CH)